Prevalence and risk factors of retro-styloid lymph node metastasis in oropharyngeal carcinoma. (31st December 2022) - Toya, Ryo; Saito, Tetsuo; Fukugawa, Yoshiyuki; Matsuyama, Tomohiko; Matsumoto, Tadashi; Shiraishi, Shinya; Murakami, Daizo; Orita, Yorihisa; Hirai, Toshinori; Oya, Natsuo
Abstract: Background: Supporting data defining the selection criteria of level VIIb for inclusion in the target volume in radiotherapy (RT) planning are insufficient. We evaluated the prevalence of level VIIb retro-styloid lymph node metastasis (RSLNM) and associated risk factors in patients with oropharyngeal carcinoma (OPC). Materials and methods: We retrospectively reviewed pre-treatment [ 18 F]-fluoro-2-deoxy-d -glucose–positron emission tomography/computed tomography (CT) along with contrast-enhanced thin slice CT and magnetic resonance (MR) images of 137 patients pathologically confirmed as having OPC who underwent RT. The location of lymph nodes (LNs) was confirmed on the planning CT images. Fisher's exact test and logistic regression analyses were made to determine the risk factors of RSLNM. Results: RSLNM was confirmed in 18 (13%) patients. All RSLNMs were located within level VIIb on the planning CT images. No patients exhibited LNM in contralateral level VIIb. Furthermore, no patients with negative or single ipsilateral cervical LNM had RSLNM. Fisher's exact test revealed that smoking status ( p =.027), multiple ipsilateral cervical LNM ( p =.045) and LN ≥15 mm in the upper limit of ipsilateral level II ( p <.001) were significantly associated with RSLNM. Logistic regression analyses revealed that the presence of LNs ≥15 mm in upper limit of ipsilateral level II was significantly associated with RSLNM (odds ratio: 977.297; 95% confidence interval: 57.629–16573.308; p <.001). Conclusions: RSLNM is relatively common in patients with OPC with a prevalence rate of approximately 10%. The prevalence of RSLNM in patients with negative or single ipsilateral cervical LNM and contralateral RSLNM is extremely low; therefore, level VIIb can be excluded from the target volume in such patients. LN ≥15 mm in the upper limit of ipsilateral level II is a risk factor for RSLNM. Ipsilateral level VIIb should be included in the target volume for patients with this risk factor. KEY MESSAGE: Retro-styloid lymph node metastasis (RSLNM) prevalence is ∼10% in oropharyngeal carcinoma. Lymph node ≥15 mm in ipsilateral level II upper limit is a risk factor for RSLNM.